Combination therapy targeting both cancer stem-like cells and bulk tumor cells for improved efficacy of breast cancer treatment. Issue 6 (2nd June 2016) - Wang, Tao; Narayanaswamy, Radhika; Ren, Huilan; Torchilin, Vladimir P.
ABSTRACT: Many types of tumors are organized in a hierarchy of heterogeneous cell populations. The cancer stem-like cells (CSCs) hypothesis suggests that tumor development and metastasis are driven by a minority population of cells, which are responsible for tumor initiation, growth and recurrences. The inability to efficiently eliminate CSCs during chemotherapy, together with CSCs being highly tumorigenic and invasive, may result in treatment failure due to cancer relapse and metastases. CSCs are emerging as a promising target for the development of translational cancer therapies. Ideal panacea for cancer would kill all malignant cells, including CSCs and bulk tumor cells. Since both chemotherapy and CSCs-specific therapy are insufficient to cure cancer, we propose combination therapy with CSCs-targeted agents and chemotherapeutics for improved breast cancer treatment. We generated in vitro mammosphere of 2 breast cancer cell lines, and demonstrated ability of mammospheres to grow and enrich cancer cells with stem-like properties, including self-renewal, multilineage differentiation and enrichment of cells expressing breast cancer stem-like cell biomarkers CD44 + /CD24 −/low . The formation of mammospheres was significantly inhibited by salinomycin, validating its pharmacological role against the cancer stem-like cells. In contrast, paclitaxel showed a minimal effect on the proliferation and growth of breast cancer stem-like cells. While combination therapies of salinomycin with conventional chemotherapy (paclitaxel or lipodox) showed a potential to improve tumor cell killing, different subtypes of breast cancer cells showed different patterns in response to the combination therapies. While optimization of combination therapy is warranted, the design of combination therapy should consider phenotypic attributes of breast cancer types.